Ideal, reality and perspectives- An exploration on role of parents of child with special educational needs in inclusive education - Yan, Peng (e-Pedagogium, 2010)
The support and involvement of parents of children with special educational needs (SEN) is vital, which links successful implementation and development of inclusive education. Firstly, this paper analyzes the ideal roles that parents of child with SEN should act in inclusive education, such as advocator, promoter and collaborator of inclusive education and lifelong learner; secondly, it discusses current role conflicts which parents of child with SEN are facing in real life, for example, advocating without clear consciousness of right, promoting inclusive education passively, cooperating with professionals negatively and learning without enough supportive resources; finally, it presents some practical and possible strategies about how to realize the ideal roles of parents of child with SEN in inclusive education.
Keywords: Parents of children with special educational needs; role; inclusive education